Global production networks and host-site industrial upgrading: the case of the semiconductor industry in Thailand. Issue 2 (2nd April 2016) - Intarakumnerd, Patarapong; Chairatana, Pun-Arj; Chaiyanajit, Preeda
Abstract: Although Thailand's electronics industry has been considered as one of the strategic sectors, the evidence in this article shows that it is dominated by midstream and downstream activities. Despite accounting for a quarter of electronics exports, semiconductors manufacturing is confined to low value-added activities. The lack of industrial policy has restricted technological upgrading in the industry. Upgrading efforts made by both public and private initiatives have so far failed. The case studies show that firms in Thailand must acquire and develop technological capabilities to stimulate the industry's transformation from low-to-high value-added activities.